Do pharmacists contribute to patients' management of symptoms suggestive of cancer: a qualitative study. (25th September 2018) - Notman, Frances; Porteous, Terry; Murchie, Peter; Bond, Christine M.
Abstract: Objectives: Limited awareness of cancer symptoms results in patient delay in seeking help and contributes to delay in diagnosis. Few UK studies have investigated the potential for community pharmacists to facilitate earlier detection of cancer. This study aimed to investigate what actions patients take to manage their early cancer symptoms, to identify the extent of current community pharmacy involvement and to consider the potential role for community pharmacists to facilitate appropriate management and appraisal of potential early cancer symptoms. Methods: Patients diagnosed with lung, colorectal or gastro‐oesophageal cancer in the preceding 12 months were identified during clinic visits by consultants. Semi‐structured interviews were conducted, audio‐recorded, transcribed and thematically analysed, using the Framework Approach. Key findings: Twenty‐five consenting patients were interviewed: two‐thirds were male and more than half had lung cancer. Although all had experienced potential cancer symptoms prior to diagnosis, most underestimated seriousness and misattributed causation. Symptoms were managed by lifestyle changes and self‐selecting medicines from local shops, supermarkets and pharmacies but without engaging with the pharmacist. Conclusions: For symptom management, participants self‐selected medicines from community pharmacies, but pharmacy staff were rarely involved. Involving community pharmacists or their staff at the point of sale of these medicines might have facilitated earlier cancer diagnosis. Further research is needed to quantify how many patients with symptoms suggestive of cancer present in community pharmacies to understand if a pharmacist's role in facilitating symptom management and appraisal of potential cancer symptoms would be acceptable and effective, before developing any interventions.